KEPEMIMPINAN POLITIK PEREMPUAN DALAM PANDANGAN ISLAM - Mashuri Mashuri (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2016)
The discussions and discourses about women leadership are never ending to be observed, both in common people as well as in the elites. There is a view that woman could be a leader with argument that woman leadership is possible as long as for the goodnessofpeople. Islamic thought recognizesmen's and women's "equality",Women have the same role as men in their leadership and actively encourage in that leadership. In other side, the refusal towards women's leadership also came from religious understanding. Women are supposed to be the guard of tradition and their responsibility is to preserve common believes to the next generation. Women are persuaded to stay at home, stay away from the public space. They criticize the women role outside of the domestic space. Women's carrier creates social disturbance. In their view, the women who work in public sector created unemployment among men because they should compete with women in work's market. The extreme view said that it is haram (forbidden) for women to become a public leader. This writing tries to explain Islamic view toward the women leadership.